Neurotoxic Reactive Astrocytes Drive Neuronal Death after Retinal Injury - Guttenplan, Kevin A.; Stafford, Benjamin K.; El-Danaf, Rana N.; Adler, Drew I.; Münch, Alexandra E.; Weigel, Maya K.; Huberman, Andrew D.; Liddelow, Shane A. (Cell reports (Cambridge), 2020)
Glaucoma is a neurodegenerative disease that features the death of retinal ganglion cells (RGCs) in the retina, often as a result of prolonged increases in intraocular pressure. We show that preventing the formation of neuroinflammatory reactive astrocytes prevents the death of RGCs normally seen in a mouse model of glaucoma. Furthermore, we show that these spared RGCs are electrophysiologically functional and thus still have potential value for the function and regeneration of the retina. Finally, we demonstrate that the death of RGCs depends on a combination of both an injury to the neurons and the presence of reactive astrocytes, suggesting a model that may explain why reactive astrocytes are toxic only in some circumstances. Altogether, these findings highlight reactive astrocytes as drivers of RGC death in a chronic neurodegenerative disease of the eye. [Display omitted] •Astrogliosis occurs following acute optic nerve injury and in a mouse model of glaucoma•Reducing astrogliosis stops neuron death after optic nerve crush or in a glaucoma model•Neurons spared from death remain electrophysiologically functional•Injury is required for neurons to become susceptible to astrocyte-mediated toxicity Guttenplan et al. show that dampening the formation of reactive astrocytes prevents neuronal death following acute optic nerve crush or in a chronic model of glaucoma, with spared neurons remaining electrophysiologically functional. More generally, they show that injury is required to induce neurons to become susceptible to astrocyte-mediated toxicity.